Zapobieganie przestępczości i sprawiedliwość karna z perspektywy Kongresów Organizacji Narodów Zjednoczonych - Pływaczewski, Emil W. (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
For over 65 years, the United Nations has held congresses aimed at strengthening international cooperation against expanding crime. The First Congress on the Prevention of Crime and Treatment of Offenders took place in Geneva in 1955. Sixty-six years later, in 2021, this tradition continued, postponed by the Covid-19 epidemic, as the Fourteenth United Nations Congress on Crime Prevention and Criminal Justice took place in the former capital of Japan — Kyoto. The aim of the paper is to present the most important achievements of all 14 congresses, especially focusing on the development of UN standards and norms in crime prevention and criminal justice. The author also presents the history of the participation and activities of Polish participants of the Congresses (official delegates and individual experts) in the years 1960–2021. The general conclusion is that the institution of the UN Crime Congresses is a major high-level forum to steer the development of the rule of law, to promote global security and good governance, and to improve the response to crime.
Keywords: Narody Zjednoczone; kongresy Organizacji Narodów Zjednoczonych; zapobieganie przestępczości i sprawiedliwość karna (postępowanie z przestępcami); standardy i normy Narodów Zjednoczonych w zakresie zapobiegania przestępczości i sprawiedliwości karnej; deklaracje kongresów ONZ